Fungsi Masjid Sebangai Sentral Dakwah Di Kota Bengkulu - Saefudin Saefudin; Japarudin Japarudin; Zulfikri Muhammad (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2012)
This research will focus on observing the development of preaching islam in Bengkulu by applying historical anthropologist that is tracking the historical background of the mosque through four levels of activities: heuristic, critique, interpretation. The finding shows that the development of islam in Bengkulu historically gives general view, the role of the mosque as the center of preaching on the mosque being observed. The mosque in Bengkulu (among three of them being observed) have present the figure of islam ‘ahlussunnh wal jamaah’ which was brought from North Sumatra. Islam which is featuring javanese culture bad left the tradition of ‘ratib jirat’ inthr mosque of syuhada between 19th to 20th century. During this period the mosque was not only used as reogious activities but also as media in discussing any problems for the soieties. This is can be seen on the book ‘simbur cahayo’ the Bengkulu act. More over the mosque had it functioms as the centre of islamic education and a place to protect them from any attack during the war